2015
DOI: 10.1177/107327481502200208
|View full text |Cite
|
Sign up to set email alerts
|

Surgical and Molecular Pathology of Barrett Esophagus

Abstract: Grading is essential for developing appropriate treatment plans, follow-up visits, and therapeutic interventions for each patient. Familiarity with current molecular testing methods will help physicians correctly diagnose the disease and select the most appropriate therapy for each of their patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…In this study, a low level of DUOX2 mRNA was found in both normal esophagus and columnar epithelium of Barrett esophagus, although a low level of DUOX2 protein was only observed in Barrett esophagus but not normal esophagus. Barrett esophageal mucosa is gastric-type mucosa with intestinal metaphasia induced by the acid-peptic gastric content, which erodes the squamous mucosa [ 26 ]. Barrett esophagus is a well-recognized risk of esophageal adenocarcinoma [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a low level of DUOX2 mRNA was found in both normal esophagus and columnar epithelium of Barrett esophagus, although a low level of DUOX2 protein was only observed in Barrett esophagus but not normal esophagus. Barrett esophageal mucosa is gastric-type mucosa with intestinal metaphasia induced by the acid-peptic gastric content, which erodes the squamous mucosa [ 26 ]. Barrett esophagus is a well-recognized risk of esophageal adenocarcinoma [ 27 ].…”
Section: Discussionmentioning
confidence: 99%